La Gestión Micro Curricular Y Los Procesos De Análisis, Comprensión E Interpretación De Los Estudiantes De La Escuela De Educación Básica “Fausto Molina Molina” Del Cantón Quevedo, Provincia De Los Ríos, Parroquia EL GUAYACÁN. - Méndez Consuegra, Maura (2014)
This thesis concerns the analysis of the micro curriculum management in relation to the processes of analysis, understanding and interpretation of the students of the School of Basic Education "Fausto Molina Molina" Quevedo Canton province of Los Ríos, The Parish Guayacán. The methodology was finalized in addressing the types of field research and literature; theoretical methods were applied as inductive, deductive and analytical; Empirical methods as survey, observation and document review. It was found that 68% of teachers do a limited curriculum micro management that negatively affect the learning process of the students because of the problems that occur in the phases of analysis, understanding and interpretation. The proposal is called "Upgrade Plan on micro management curriculum development processes analysis, understanding and interpretation students of the School of Basic Education" Fausto Molina Molina "Quevedo Canton" and is expected to produce the solutions to problems (as expected results). Keywords: micro curriculum, process analysis, interpretation, performance management."